Unlocking Students’ Understanding: Implementing the TTWE Strategy in Reading Activities - Saiful (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study explored the effectiveness of the Thinking, Talking, Writing, and Evaluation (TTWE) Strategy in enhancing reading comprehension among second-grade students at SMPN 1 Mare. A total of 20 students participated in the research. The data were collected through pre-experimental research with Pre-test and Post-test assessments. The Pre-test measured students’ initial reading comprehension abilities, while the Post-test evaluated their progress after the intervention. Results showed that the average Pre-test score was 56.05, indicating limited comprehension skills. Many students struggled with identifying main ideas, vocabulary, and implicit meanings within texts. After applying the TTWE Strategy, the Post-test average increased significantly to 80.1. The improvement was evident in both score range and classification, with several students achieving higher performance levels. The TTWE Strategy encouraged active learning through small group discussions, collaborative responses, and peer evaluations, which promoted deeper understanding and critical thinking. The engaging and interactive nature of the activities contributed to students' enthusiasm and participation during lessons. Statistical analysis using a t-test confirmed a significant difference between Pre-test and Post-test results, with the t-test value surpassing the critical value at the 0.05 significance level. These findings suggest that the TTWE Strategy is an effective approach to improving reading comprehension among junior high school students.